Method for producing composite for secondary battery electrode

The mechanochemical mixing of electrode active material with fibrous carbon in a non-slurry form addresses the energy and uniformity issues in composite particle production, resulting in high-conductivity composite particles for secondary batteries with reduced energy consumption and improved battery performance.

JP2025007101APending Publication Date: 2025-01-17TOYO INK MFG CO LTD

Patent Information

Application Number
JP2023108282
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing methods for producing composite particles for secondary battery electrodes require high energy for solvent drying and struggle with uniform distribution of fibrous carbon, leading to non-uniform conductive networks and increased energy consumption.

Method used

A method involving mechanochemical mixing of electrode active material with fibrous carbon dispersion using a non-slurry form, followed by solvent removal, to achieve uniform adsorption and reduce drying energy, utilizing a dispersant with specific Mooney viscosity and phase angle characteristics.

Benefits of technology

This approach results in composite particles with high conductivity and cohesive strength, enabling high-output, long-life nonaqueous electrolyte secondary batteries with reduced energy consumption and improved electrode uniformity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007101000001
    Figure 2025007101000001
  • Figure 2025007101000002
    Figure 2025007101000002
  • Figure 2025007101000003
    Figure 2025007101000003
Patent Text Reader

Abstract

To provide a method for producing a composite for a secondary battery electrode having excellent electrical conductivity by precisely controlling the dispersion state of fibrous carbon on an active material.SOLUTION: A method for producing a composite for a secondary battery electrode containing an electrode active material and fibrous carbon includes a step of combining an electrode active material and a fibrous carbon dispersion in which the fibrous carbon is dispersed in a solvent in a non-slurry state by using a mechanochemical mixer, and a step of removing the solvent and drying the composite. The fibrous carbon dispersion contains fibrous carbon, a dispersant, and a solvent. The dispersant contains a copolymer A containing a nitrile-group-containing structural unit and an aliphatic hydrocarbon structural unit. The Mooney viscosity (ML1+4,100°C) of the copolymer A is 10 to 70, and the phase angle of the fibrous carbon dispersion at a frequency of 1 Hz measured by dynamic viscoelasticity measurement is 19° or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a composite for a secondary battery electrode. [Background technology]

[0002] With the spread of electric vehicles and the miniaturization, weight reduction, and high performance of portable devices, secondary batteries with high energy density and higher capacity are required. Under such a background, non-aqueous electrolyte secondary batteries using a non-aqueous electrolyte, particularly lithium ion secondary batteries, are being used in many devices because of their characteristics of high energy density and high voltage.

[0003] Furthermore, as the applications of lithium-ion secondary batteries expand, there is a demand not only for improved battery performance, such as higher capacity, faster charging, and longer life, but also for reduced battery costs and a reduced environmental impact in production. In particular, there is a growing need to reduce the environmental impact, which in turn leads to reduced CO2 emissions, and the reduction of energy consumption in the production of lithium-ion secondary batteries, which account for a large portion of the costs and energy consumed in the production of electric vehicles, has become an issue.

[0004] To address the above issues, a method of manufacturing electrodes by powder molding that does not require a composite slurry has been proposed, since a large amount of drying energy is required to remove the solvent in conventional electrode manufacturing methods that use a composite slurry. In electrode manufacturing by powder molding, issues include improving productivity and making the electrode material uniform, so composite particles of active materials are used, which are expected to improve the fluidity of the material and narrow the particle size distribution. For example, Patent Document 1 discloses a method for increasing thickness accuracy at low basis weight during powder molding by controlling the particle size distribution of composite particles produced by spraying and drying a slurry for composite particles containing an electrode active material, a water-soluble polymer, a binder resin, and a dispersion medium. Furthermore, Patent Document 2 discloses an example of producing composite particles with excellent particle strength by spray granulating a slurry containing a positive electrode active material, carbon black, and cellulose nanofibers. In addition, composite particles of active materials are expected to be used not only in powder molding, but also in conventional manufacturing processes using composite slurries. In order to increase the capacity of secondary batteries, it is essential to increase the active material ratio in the electrode, so it is necessary to reduce the amount of auxiliary components. For this reason, the use of fibrous carbon, which has a small outer diameter and long fiber length and can form a conductive network with a small amount of addition, is seen as a promising conductive agent. However, it is difficult to distribute it uniformly in the electrode because it conflicts with the large cohesive force. Therefore, a method has been proposed that uses composite particles with fibrous carbon adsorbed on the surface of the active material in advance. For example, Patent Document 3 discloses an example in which positive electrode active material particles and fibrous carbon are dispersed in a solvent using an ultrasonic disperser, and the resulting slurry is spray-granulated to produce composite particles in which the materials are uniformly mixed, and the composite particles are then made into an electrode after preparing a composite slurry. Furthermore, Patent Document 4 discloses an example in which a positive electrode active material and carbon nanotubes are combined in a nitrogen atmosphere by mechanochemical treatment to produce a positive electrode active material having high electronic conductivity and high mechanical strength. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 6954424 [Patent Document 2] Patent No. 6380526 [Patent Document 3] Patent No. 5377946 [Patent Document 4] JP 2016-201228 A Summary of the Invention [Problem to be solved by the invention]

[0006] The methods disclosed in Patent Documents 1 to 3 require a spray granulation process when producing composite particles. A slurry in which the materials are uniformly dispersed is sprayed and instantly dried in a heating tank, making it possible to produce homogeneous composite particles. However, in order to spray the slurry in a spray form, it is necessary to reduce the viscosity of the slurry, and there is a limit to how much solid can be produced. Therefore, a larger amount of solvent is required than that used in conventional composite slurries, and the effect of reducing energy consumption in electrode production is not significant. In the method disclosed in Patent Document 4, composite particles can be produced without using a solvent because the carbon nanotubes are mixed in a powder state. However, it is difficult to disentangle the fibrous and entangled carbon nanotubes during the composite process, and the carbon nanotubes are not uniformly adsorbed onto the active material surface, resulting in non-uniform composite particles, making it difficult to form a uniform conductive network in the electrode.

[0007] The present invention aims to provide composite particles that can solve the above-mentioned problems, i.e., reduce the drying energy required to remove the solvent during electrode production, while also achieving a uniform composite of highly cohesive fibrous carbon and active material, and to provide a composite for secondary battery electrodes that can achieve high conductivity even in the electrode. [Means for solving the problem]

[0008] The present invention relates to a method for producing a composite for a secondary battery electrode, comprising: The method includes a step of combining an electrode active material and a fibrous carbon dispersion in which fibrous carbon is dispersed in a solvent in a non-slurry state using a mechanochemical mixer, and a step of removing the solvent and drying the mixture, The fibrous carbon dispersion contains fibrous carbon, a dispersant, and a solvent, The dispersant comprises a copolymer A containing a nitrile group-containing structural unit and an aliphatic hydrocarbon structural unit, The Mooney viscosity (ML 1+4 ,100℃) is 10 to 70, The present invention relates to a method for producing a composite for a secondary battery electrode, wherein the fibrous carbon dispersion has a phase angle of 19° or more at a frequency of 1 Hz as measured by dynamic viscoelasticity measurement.

[0009] The present invention relates to the above-mentioned method for producing a composite for a secondary battery electrode, wherein the complex modulus of the fibrous carbon dispersion as determined by dynamic viscoelasticity measurement is less than 20 Pa.

[0010] The present invention relates to the method for producing the composite for a secondary battery electrode, wherein the content of the nitrile group-containing structural unit is 15 mass% or more and 50 mass% or less, and the content of the aliphatic hydrocarbon structural unit is 40 mass% or more and less than 85 mass%, based on the mass of the copolymer A.

[0011] The present invention relates to the method for producing the composite for a secondary battery electrode, wherein the composite for a secondary battery electrode has an exothermic peak temperature of 520°C or less, as determined by simultaneous thermogravimetry and differential thermal analysis under an oxygen atmosphere, and a volume resistivity of 100 Ω cm or less under a load of 20 kN.

[0012] The present invention relates to a method for producing the composite for a secondary battery electrode, wherein the composite for a secondary battery electrode contains a binder resin.

[0013] The present invention also relates to a method for producing an electrode film, comprising producing an electrode composite for a secondary battery according to the above method, and forming an electrode film using the electrode composite for a secondary battery.

[0014] The present invention relates to a method for producing a secondary battery, comprising producing an electrode composite for a secondary battery according to the above method, and forming an electrode film using the electrode composite for a secondary battery. Effect of the Invention

[0015] According to an embodiment of the present invention, a composite for a secondary battery electrode having excellent electrical conductivity can be provided by precisely controlling the dispersion state of the fibrous carbon on the active material. According to still another embodiment of the present invention, a high-output, long-life non-aqueous electrolyte secondary battery and an electrode film used therein can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, a method for producing a composite for a secondary battery electrode according to an embodiment of the present invention will be described in detail. The present invention is not limited to the following embodiment, and the present invention also includes embodiments that are implemented within the scope of the present invention.

[0017] In this specification, carbon nanotubes may be referred to as "CNTs." Hydrogenated nitrile rubber may be referred to as "H-NBR," and N-methyl-2-pyrrolidone may be referred to as "NMP." In this specification, carbon nanotube dispersions may be simply referred to as "CNT dispersions" or "dispersions." Additionally, composites for secondary battery electrodes may be referred to as "composite for electrodes" or "composite."

[0018] <Method of manufacturing a composite for secondary battery electrode> The method for producing an electrode composite for a secondary battery of the present invention is characterized by including a step of combining an electrode active material and a fibrous carbon dispersion in which fibrous carbon is dispersed in a solvent in a non-slurry state using a mechanochemical mixer, and a step of removing the solvent and drying the resulting mixture.

[0019] In the process for producing the composite for secondary battery electrode of the present invention, the inclusion of the following (1) to (3) is an important factor for producing a composite having good resistance characteristics. (1) Uses a dispersion of fibrous carbon (2) Controlling the state of the mixture of the electrode active material and the dispersed carbon fiber (3) Compounding in a mechanochemical mixer The reasons for this will be explained below. (1) In order to adsorb fibrous carbon to the surface of an active material in the form of disintegrated primary particles or bundle particles, it is necessary to disintegrate the fibrous carbon, which has strong cohesive power, to the above-mentioned state, and dispersion in a liquid phase state (slurry) is essential for this. However, if it is combined with an active material in a slurry state, it is not possible to reduce the energy required to dry the solvent involved in electrode production. Therefore, it is necessary to use a dispersion of fibrous carbon in which the primary particles or bundle particles of fibrous carbon are uniformly dispersed and stabilized in advance. (2) By forming a composite in a non-slurry state with a high solid content concentration, it is possible to reduce the total amount of energy required to dry the solvent compared to the conventional electrode manufacturing method using a composite slurry. In addition, since a non-slurry mixture does not have fluidity as a liquid, separation of components during drying and drying aggregation of fibrous carbon can be suppressed even if the composition contains less resin components than a typical composite slurry. It is preferable that the solid content concentration of the non-slurry mixture is 80 mass % or more. The form of the mixture changes as follows depending on the solvent content. From the highest solvent content, the form is slurry (has liquid fluidity), clay (no liquid fluidity, sticky), crumbly (no liquid fluidity, no stickiness), and powder (absolutely dry). In this invention, non-slurry refers to clay or crumbly. These changes in form have a large effect not only on the appearance, but also on the mixing state of the mixture. It is more preferable for the mixture form in the composite of the present invention to be a crumbly mixture, as this can suppress drying and agglomeration of the fibrous carbon during the solvent removal process. (3) By mixing in a non-slurry state, it is expected that drying aggregation can be suppressed, but since it cannot flow as a liquid, the dispersion of fibrous carbon is difficult to wet and spread on the active material surface, and it is likely to become uneven. Therefore, by using a mechanochemical mixer capable of applying shear force to press the dispersion of fibrous carbon against the active material surface and promote wetting and spreading, it is expected that the fibrous carbon can be evenly adsorbed onto the active material surface while loosening the fibrous carbon. The above (1) to (3) make it possible to reduce the amount of drying energy required to prepare an electrode, to allow the fibrous carbon to be evenly adsorbed onto the surface of the active material in a loosened state, and to prevent separation of the components and aggregation of the fibrous carbon during drying during the process of concentrating and evaporating the solvent, thereby enabling the production of a highly conductive composite and electrode.

[0020] <Combining process using mechanochemical mixer> The mechanochemical mixer is not particularly limited as long as it is a device capable of mixing a non-slurry mixture by applying a shear force. Examples of such machines include high-speed mixers such as the Henschel Mixer and Super Mixer, particle compounding devices "Nanocure", "Nobilta", and "Mechanofusion" manufactured by Hosokawa Micron Corporation, powder surface modification device "Miraro" manufactured by Nara Machinery Works, "Hivismix" and "Hivisdepermix" manufactured by Primix, mixers "Planetary Mixer" and "Trimix" manufactured by Inoue Manufacturing Co., Ltd., and mixer / granulator "High Speed ​​Mixer" manufactured by EarthTechnica Corporation. Among the mechanochemical mixers, planetary mixers, Trimix, Mechanofusion, and Nobilta are preferred because they are capable of shear compounding and uniform mixing of materials.

[0021] <Electrode active material> The electrode active material is a material that causes a battery reaction required to extract electrical energy, and is not particularly limited. As the positive electrode active material, for example, for secondary battery applications, metal compounds such as metal oxides and metal sulfides that can reversibly dope or intercalate lithium ions can be used. For example, lithium manganese composite oxides (e.g., Li x Mn2O4 or Li x MnO2), lithium nickel composite oxide (e.g. Li x NiO2), lithium cobalt complex oxide (Li x CoO2), lithium nickel cobalt complex oxide (e.g. Li x Ni 1-y Co y O2), lithium manganese cobalt complex oxide (e.g. Li x Mn y Co 1-y O2), lithium nickel manganese cobalt composite oxide (e.g. Li x Ni y Co z Mn 1-y-z O2), spinel-type lithium manganese nickel composite oxide (e.g. Li x Mn 2-y Ni y O4), lithium phosphate powder with an olivine structure (e.g. Li x FePO4, Lix Fe 1-y Mn y PO4, Li x CoPO4, etc.), manganese oxide, iron oxide, copper oxide, nickel oxide, vanadium oxide (e.g., V2O5, V6O 13 )), transition metal oxide powders such as titanium oxide, iron sulfate (Fe2(SO4)3), transition metal sulfide powders such as TiS2, and FeS, etc. However, x, y, and z are numbers, where 0 < x < 1, 0 < y < 1, 0 < z < 1, and 0 < y + z < 1. These cathode active materials can also be used alone or in combination. Among these active materials, in particular, active materials containing Ni and / or Mn (especially when the total amount of Ni and / or Mn in the transition metal is 50 mol% or more) tend to become highly basic due to the elution of raw material-derived components or metal ions, and as a result, gelation of the binder resin and deterioration of the dispersion state are likely to occur. Therefore, in the case of a battery containing an active material containing Ni and / or Mn, this embodiment is particularly effective.

[0022] As the anode active material, for example, metallic Li that can reversibly dope or intercalate lithium ions, or its alloy, tin alloy, silicon-based materials (such as metallic Si, Si alloy, SiOx), metal oxide-based materials such as LiXTiO2, LiXFe2O3, LiXFe3O4, LiXWO2, conductive polymers such as polyacetylene and poly-p-phenylene, artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, and resin-fired carbon materials can be used. However, x is a number, where 0 < x < 1. These anode active materials can also be used alone or in combination. In particular, when using a silicon-based material, although the theoretical capacity is large, the volume expansion is extremely large. Therefore, it is preferably used in combination with artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, and resin-fired carbon materials.

[0023] <Fibrous carbon> Fibrous carbon is a fibrous carbon material, and has a high aspect ratio in the long axis direction, making it easier to form a conductive network compared to particulate carbon such as carbon black. Examples of fibrous carbon include carbon fiber (CNF) and carbon nanotube (CNT). CNTs are flat graphite rolled into a cylindrical shape, and include single-walled CNTs, double-walled CNTs, thin-walled (several-walled) CNTs, and multi-walled CNTs, and these may be mixed. Single-walled CNTs have a structure in which one layer of graphite is rolled. Multi-walled CNTs have a structure in which two or more layers of graphite are rolled. In addition, the sidewalls of CNTs do not have to have a graphite structure. In addition, for example, CNTs with sidewalls having an amorphous structure are also CNTs in this specification.

[0024] The shape of the CNT is not limited. Examples of such shapes include various shapes including needle-like, cylindrical tube-like, fishbone-like (fishbone or cup stack type), trump-like (platelet) and coil-like. Among them, the shape of the CNT is preferably needle-like or cylindrical tube-like. The CNT may be a single shape or a combination of two or more shapes.

[0025] Examples of the form of CNT include graphite whiskers, filamentous carbon, graphite fibers, ultrafine carbon tubes, carbon tubes, carbon fibrils, carbon microtubes, and carbon nanofibers. The carbon nanotubes may have a single form or a combination of two or more of these forms.

[0026] The average outer diameter of the fibrous carbon is preferably 100 nm or less, more preferably 50 nm or less. If the average outer diameter is too large, it may be difficult to uniformly combine with the composite. Also, it is preferably 30 nm or less, more preferably 20 nm or less, and even more preferably 13 nm or less. Also, it is preferably 1 nm or more, and more preferably 3 nm or more. The average outer diameter of the fibrous carbon can be calculated by observing and photographing the fibrous carbon with a transmission electron microscope, randomly selecting 300 pieces of fibrous carbon from the observation photograph, and measuring the outer diameter of each piece.

[0027] <Dispersant> The dispersant contains a copolymer A containing an aliphatic hydrocarbon structural unit and a nitrile group-containing unit. The conductive material dispersion of the present invention has a Mooney viscosity (ML 1+4 , 100°C) is 10 or more and 70 or less.

[0028] The aliphatic hydrocarbon structural unit is a structural unit containing an aliphatic hydrocarbon structure, and is preferably a structural unit consisting of only an aliphatic hydrocarbon structure. The aliphatic hydrocarbon structure contains at least a saturated aliphatic hydrocarbon structure, and may further contain an unsaturated aliphatic hydrocarbon structure. The aliphatic hydrocarbon structure preferably contains at least a linear aliphatic hydrocarbon structure, and may further contain a branched aliphatic hydrocarbon structure.

[0029] Examples of the aliphatic hydrocarbon structural unit include an alkylene structural unit, an alkenylene structural unit, an alkyl structural unit, an alkanetriyl structural unit, an alkanetetrayl structural unit, etc. The aliphatic hydrocarbon structural unit preferably contains at least an alkylene structural unit.

[0030] The alkylene structural unit is a structural unit containing an alkylene structure, and is preferably a structural unit consisting of only an alkylene structure. The alkylene structure is preferably a linear alkylene structure or a branched alkylene structure.

[0031] The alkylene structural unit preferably contains a structural unit represented by the following general formula (1A).

[0032] General formula (1A) [ka]

[0033] In general formula (1A), n represents an integer of 1 or more. n is preferably an integer of 2 or more, more preferably an integer of 3 or more, and particularly preferably an integer of 4 or more. n is preferably an integer of 6 or less, and more preferably an integer of 5 or less. In particular, n is preferably 4. In this specification, "*" represents a bond to another structure.

[0034] The alkylene structural unit preferably contains a structural unit represented by the following general formula (1B).

[0035] General formula (1B) [ka]

[0036] In general formula (1B), n represents an integer of 1 or more. n is preferably an integer of 2 or more, and more preferably an integer of 3 or more. n is preferably an integer of 5 or less, and more preferably an integer of 4 or less. In particular, n is preferably 3.

[0037] The alkylene structural unit preferably contains a structural unit represented by the following general formula (1C).

[0038] General formula (1C) [ka]

[0039] In general formula (1C), n represents an integer of 1 or more. n is preferably an integer of 4 or less, more preferably an integer of 3 or less, and even more preferably an integer of 2 or less. In particular, n is preferably 2.

[0040] The method for introducing an alkylene structural unit into Copolymer A is not particularly limited, and examples thereof include the following method (1a) or (1b).

[0041] In the method (1a), a copolymer is prepared by polymerization reaction using a monomer composition containing a conjugated diene monomer. The prepared copolymer contains a monomer unit derived from the conjugated diene monomer. In the present invention, the "monomer unit derived from the conjugated diene monomer" may be referred to as the "conjugated diene monomer unit", and the monomer unit derived from other monomers may be omitted in the same manner. Next, the conjugated diene monomer unit is hydrogenated to convert at least a part of the conjugated diene monomer unit into an alkylene structural unit. Hereinafter, "hydrogenation" may be referred to as "hydrogenation". The finally obtained copolymer A contains the unit obtained by hydrogenating the conjugated diene monomer unit as an alkylene structural unit.

[0042] The conjugated diene monomer unit includes at least a monomer unit having one carbon-carbon double bond. For example, the 1,3-butadiene monomer unit, which is a conjugated diene monomer unit, includes at least one monomer unit selected from the group consisting of a monomer unit having a cis-1,4 structure, a monomer unit having a trans-1,4 structure, and a monomer unit having a 1,2 structure, and may include two or more monomer units. The conjugated diene monomer unit may further include a monomer unit having no carbon-carbon double bond and including a branch point. In this specification, the "branch point" refers to a branch point in a branched polymer, and when the conjugated diene monomer unit includes a monomer unit having a branch point, the above prepared copolymer and copolymer A are branched polymers.

[0043] In the method (1b), a copolymer is prepared by polymerization reaction using a monomer composition containing an α-olefin monomer. The prepared copolymer contains α-olefin monomer units. The finally obtained copolymer A contains α-olefin monomer units as alkylene structural units.

[0044] Among these, the method (1a) is preferred because the copolymer can be easily produced. The carbon number of the conjugated diene monomer is 4 or more, preferably 4 to 6. Examples of the conjugated diene monomer include conjugated diene compounds such as 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, and 1,3-pentadiene. Among these, 1,3-butadiene is preferred. The alkylene structural unit preferably contains a structural unit (hydrogenated conjugated diene monomer unit) obtained by hydrogenating a conjugated diene monomer unit, and more preferably contains a structural unit (hydrogenated 1,3-butadiene monomer unit) obtained by hydrogenating a 1,3-butadiene monomer unit. The conjugated diene monomer can be used alone or in combination of two or more kinds.

[0045] The hydrogenation is preferably a method capable of selectively hydrogenating conjugated diene monomer units. Examples of the hydrogenation method include known methods such as oil phase hydrogenation and aqueous phase hydrogenation.

[0046] The hydrogenation can be carried out by a conventional method. For example, the hydrogenation can be carried out by treating a copolymer having conjugated diene monomer units dissolved in a suitable solvent with hydrogen gas in the presence of a hydrogenation catalyst. Examples of the hydrogenation catalyst include iron, nickel, palladium, platinum, and copper.

[0047] In the method (1b), the carbon number of the α-olefin monomer is 2 or more, preferably 3 or more, and more preferably 4 or more. The carbon number of the α-olefin monomer is preferably 6 or less, and more preferably 5 or less. Examples of the α-olefin monomer include α-olefin compounds such as ethylene, propylene, 1-butene, and 1-hexene. The α-olefin monomer may be used alone or in combination of two or more.

[0048] The alkylene structural unit preferably includes at least one selected from the group consisting of structural units containing a linear alkylene structure and structural units containing a branched alkylene structure, more preferably includes at least one selected from the group consisting of structural units consisting only of linear alkylene structures and structural units consisting only of branched alkylene structures, and further preferably includes at least one selected from the group consisting of structural units represented by the above formula (1B) and structural units represented by the above formula (1C).

[0049] The alkylene structural unit may include a structural unit containing a linear alkylene structure and a structural unit containing a branched alkylene structure. When the alkylene structural unit includes a structural unit containing a linear alkylene structure and a structural unit containing a branched alkylene structure, the content of the branched alkylene structure is preferably 70% by mass or less, more preferably 65% ​​by mass or less, based on the mass of the alkylene structural unit (i.e., when the mass of the alkylene structural unit is 100% by mass). In particular, it is preferably 20% by mass or less, more preferably 18% by mass or less, and even more preferably 15% by mass or less. When the copolymer A includes a structural unit containing a linear alkylene structure and a structural unit containing a branched alkylene structure, the content of the branched alkylene structure is, for example, 1% by mass or more, may be 5% by mass or more, or may be 10% by mass or more, based on the mass of the alkylene structural unit (i.e., when the mass of the alkylene structural unit is 100% by mass).

[0050] In the aliphatic hydrocarbon structural unit, the content of the alkylene structural unit is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more, based on the total mass of the aliphatic hydrocarbon structural units (i.e., when the mass of the aliphatic hydrocarbon structural units is 100% by mass). The content of the alkylene structural unit is, based on the total mass of the aliphatic hydrocarbon structural units (i.e., when the mass of the aliphatic hydrocarbon structural units is 100% by mass), for example, less than 100% by mass, and may be 99.5% by mass or less, 99% by mass or less, or 98% by mass or less. The content of the alkylene structural unit may be 100% by mass.

[0051] The content of the aliphatic hydrocarbon structural unit is preferably 40% by mass or more, more preferably 50% by mass or more, and even more preferably 60% by mass or more, based on the mass of copolymer A (i.e., when the mass of copolymer A is 100% by mass). The content of the aliphatic hydrocarbon structural unit is preferably less than 85% by mass, more preferably 75% by mass or less, and even more preferably 70% by mass or less, based on the mass of copolymer A (i.e., when the mass of copolymer I is 100% by mass).

[0052] The nitrile group-containing structural unit is a structural unit containing a nitrile group, preferably a structural unit containing an alkylene structure substituted with a nitrile group, more preferably a structural unit consisting of only an alkylene structure substituted with a nitrile group. The alkylene structure is preferably a linear or branched alkylene structure. The nitrile group-containing structural unit may further contain a structural unit containing (or consisting of) an alkyl structure substituted with a nitrile group. The number of nitrile groups contained in the nitrile group-containing structural unit is preferably one.

[0053] The nitrile group-containing structural unit preferably contains a structural unit represented by the following general formula (2A).

[0054] General formula (2A) [ka]

[0055] In formula (2A), n represents an integer of 2 or more. n is preferably an integer of 6 or less, more preferably an integer of 4 or less, and even more preferably an integer of 3 or less. In particular, n is preferably 2.

[0056] The nitrile group-containing structural unit preferably contains a structural unit represented by the following general formula (2B).

[0057] General formula (2B) [ka]

[0058] In formula (2B), R represents a hydrogen atom or a methyl group. R is preferably a hydrogen atom.

[0059] The method of introducing the nitrile group-containing structural unit into the copolymer A is not particularly limited, but a method of preparing a copolymer by polymerization reaction using a monomer composition containing a nitrile group-containing monomer (method (2a)) can be preferably used. The finally obtained copolymer A contains a nitrile group-containing monomer unit as a nitrile group-containing structural unit. Examples of the nitrile group-containing monomer capable of forming the nitrile group-containing structural unit include a monomer containing a polymerizable carbon-carbon double bond and a nitrile group. For example, an α,β-ethylenically unsaturated group-containing compound having a nitrile group can be mentioned, and specifically, acrylonitrile, methacrylonitrile, etc. can be mentioned. In particular, from the viewpoint of increasing the intermolecular force between the copolymers A and / or between the copolymer A and the dispersed substance (adsorbed substance), it is preferable that the nitrile group-containing monomer contains acrylonitrile. The nitrile group-containing monomer can be used alone or in combination of two or more kinds.

[0060] The content of the nitrile group-containing structural unit is preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more, based on the mass of copolymer A (i.e., when the mass of copolymer A is 100% by mass). The content of the nitrile group-containing structural unit is preferably 50% by mass or less, more preferably 46% by mass or less, and even more preferably 40% by mass or less, based on the mass of copolymer A (i.e., when the mass of copolymer A is 100% by mass). By setting the content of the nitrile group-containing structural unit within the above range, it is possible to control the adsorption to the dispersed material and the affinity to the dispersion medium, and the dispersed material can be stably present in the dispersion medium. In addition, the affinity of copolymer A to the electrolyte can be controlled, and it is possible to prevent problems such as copolymer A dissolving in the electrolyte in the battery and increasing the resistance of the electrolyte.

[0061] Copolymer A may contain any structural unit. Examples of the structural unit include an amide group-containing structural unit, a carboxyl group-containing structural unit, an alkenylene structural unit, an alkyl structural unit, and a structural unit containing a branch point such as an alkanetriyl structural unit or an alkanetetrayl structural unit. The structural unit containing a branch point is a structural unit different from the structural unit containing a branched alkylene structure and the structural unit containing a branched alkyl structure.

[0062] The amide group-containing structural unit is a structural unit containing an amide group, preferably a structural unit containing an alkylene structure substituted with an amide group, more preferably a structural unit consisting of only an alkylene structure substituted with an amide group. The alkylene structure is preferably a linear or branched alkylene structure. The amide group-containing structural unit may further contain a structural unit containing (or consisting of) an alkyl structure substituted with an amide group. The number of amide groups contained in the amide group-containing structural unit is preferably one.

[0063] The amide group-containing structural unit preferably contains a structural unit represented by the following general formula (3A).

[0064] General formula (3A) [ka]

[0065] In the general formula (3A), n represents an integer of 2 or more. n is preferably an integer of 6 or less, more preferably an integer of 4 or less, and even more preferably an integer of 3 or less. In particular, n is preferably 2. Each R' independently represents a hydrogen atom or a substituent. The substituent is preferably an alkyl group or a hydroxyalkyl group. It is preferable that at least one R' is a hydrogen atom, and more preferably two R' are hydrogen atoms.

[0066] The amide group-containing structural unit preferably contains a structural unit represented by the following general formula (3B).

[0067] General formula (3B) [ka]

[0068] In the general formula (3B), R represents a hydrogen atom or a methyl group. R is preferably a hydrogen atom. Each R' independently represents a hydrogen atom or a substituent. The substituent is preferably an alkyl group or a hydroxyalkyl group. At least one R' is preferably a hydrogen atom, and more preferably two R's are hydrogen atoms.

[0069] The method for introducing an amide group-containing structural unit into Copolymer A is not particularly limited, and examples thereof include the following method (3a).

[0070] In the method (3a), a copolymer is prepared by polymerization reaction using a monomer composition containing an amide group-containing monomer. The prepared copolymer contains amide group-containing monomer units. The finally obtained copolymer A contains the amide group-containing monomer units as amide group-containing structural units.

[0071] Examples of the amide group-containing monomer include monoalkyl (meth)acrylamides such as (meth)acrylamide, N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-propyl (meth)acrylamide, and N-isopropyl (meth)acrylamide; dialkyl (meth)acrylamides such as N,N-dimethyl (meth)acrylamide and N,N-diethyl (meth)acrylamide; N-(hydroxyalkyl) (meth)acrylamides such as N-(2-hydroxyethyl) (meth)acrylamide, N-(2-hydroxypropyl) (meth)acrylamide, and N-(2-hydroxybutyl) (meth)acrylamide; diacetone (meth)acrylamide; and acryloylmorpholine. In this specification, "(meth)acryl" refers to acryl or methacryl. In particular, the amide group-containing monomer preferably contains at least one selected from the group consisting of acrylamide, methacrylamide, and N,N-dimethylacrylamide. The amide group-containing monomer may be used alone or in combination of two or more.

[0072] The content of the amide group-containing structural unit is preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 3% by mass or less, and particularly preferably 1% by mass or less, based on the mass of copolymer A (i.e., when the mass of copolymer A is 100% by mass). When the content of the amide group-containing structural unit is within the above range, it is possible to prevent the problem of gelation of the conductive material dispersion during storage, which may occur when hydrogen bonds between copolymers A become too strong.

[0073] The carboxyl group-containing structural unit is a structural unit containing a carboxyl group, preferably a structural unit containing an alkylene structure substituted with a carboxyl group, more preferably a structural unit consisting of only an alkylene structure substituted with a carboxyl group. The alkylene structure is preferably a linear or branched alkylene structure. The carboxyl group-containing structural unit may further contain a structural unit containing (or consisting of) an alkyl structure substituted with a carboxyl group. The number of carboxyl groups contained in the carboxyl group-containing structural unit is preferably one or two. By including a carboxyl group-containing structural unit in the copolymer A, the adsorption force to the dispersed material can be improved, and the viscosity of the conductive material dispersion can be reduced, thereby improving the dispersion efficiency.

[0074] The carboxyl group-containing structural unit preferably contains a structural unit represented by the following general formula (4A).

[0075] General formula (4A) [ka]

[0076] In formula (4A), n represents an integer of 2 or more. n is preferably an integer of 6 or less, more preferably an integer of 4 or less, and even more preferably an integer of 3 or less. In particular, n is preferably 2.

[0077] The carboxyl group-containing structural unit preferably contains a structural unit represented by the following general formula (4B).

[0078] General formula (4B) [ka]

[0079] In formula (4B), R represents a hydrogen atom or a methyl group. R is preferably a hydrogen atom.

[0080] The method for introducing the carboxyl group-containing structural unit is not particularly limited, but examples thereof include the following method (4a) or (4b).

[0081] In the method (4a), a copolymer is prepared by polymerization reaction using a composition containing a carboxyl group-containing monomer. The prepared copolymer contains a carboxyl group-containing monomer unit. The finally obtained copolymer A contains the carboxyl group-containing monomer unit as a carboxyl group-containing structural unit.

[0082] In the method (4b), a copolymer containing an amide group-containing structural unit is first prepared by the method (3a) or the like. Next, the amide group contained in the amide group-containing structural unit is hydrolyzed in an acidic atmosphere to convert the amide group-containing structural unit into a carboxyl group-containing structural unit. The copolymer A finally obtained contains, as a carboxyl group-containing structural unit, a unit obtained by modifying the amide group contained in the amide group-containing structural unit by hydrolysis.

[0083] In the method (4a), examples of the carboxyl group-containing monomer include unsaturated monocarboxylic acids such as (meth)acrylic acid, crotonic acid, and isocrotonic acid; and unsaturated dicarboxylic acids such as maleic acid, fumaric acid, citraconic acid, mesaconic acid, glutaconic acid, and itaconic acid. In particular, the carboxyl group-containing monomer preferably contains at least one selected from the group consisting of acrylic acid and maleic acid. The carboxyl group-containing monomer may be used alone or in combination of two or more.

[0084] In the method (4b), in order to create an acidic atmosphere, at least one acid selected from the group consisting of inorganic acids and organic acids can be used.

[0085] Examples of inorganic acids include hydrochloric acid, nitric acid, phosphoric acid, sulfuric acid, boric acid, hydrofluoric acid, etc. Examples of organic acids include formic acid, acetic acid, citric acid, oxalic acid, succinic acid, malic acid, benzoic acid, benzenesulfonic acid, etc. Among these, succinic acid and citric acid are preferred.

[0086] The amount of the acid used is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more, based on the mass of the copolymer. The amount of the acid used is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less, based on the mass of the copolymer. If the amount used is too small, the amide group tends not to denature due to hydrolysis. If the amount used is too large, it may cause corrosion of the dispersion device and / or the inside of the battery.

[0087] The content of the carboxyl group-containing structural unit is preferably less than 1 mass %, more preferably 0.5 mass % or less, and even more preferably 0.3 mass % or less, based on the mass of copolymer A (i.e., when the mass of copolymer A is 100 mass %). If the content of the carboxyl group-containing structural unit is less than (or less than) the above range, the problem of gelation of the conductive material dispersion during storage, which may occur when hydrogen bonds between copolymers A become too strong, as described below, can be prevented.

[0088] The alkenylene structural unit is a structural unit containing an alkenylene structure, and is preferably a structural unit consisting of only an alkenylene structure. The alkenylene structure is preferably a linear alkenylene structure or a branched alkenylene structure.

[0089] The alkenylene structural unit preferably includes at least one selected from the group consisting of a structural unit containing a linear alkenylene structure and a structural unit containing a branched alkenylene structure, and more preferably includes at least one selected from the group consisting of a structural unit consisting only of a linear alkenylene structure and a structural unit consisting only of a branched alkenylene structure.

[0090] For example, when copolymer A is obtained through the above method (1a), a conjugated diene monomer unit having a carbon-carbon double bond within the unit may remain within the molecule without being hydrogenated in copolymer A. The finally obtained copolymer A may contain a conjugated diene monomer unit having a carbon-carbon double bond within the unit as an alkenylene structural unit.

[0091] The alkyl structural unit is a structural unit containing an alkyl structure (however, it is a structural unit that does not fall under other aliphatic hydrocarbon structural units such as branched alkylene structural units, nitrile group-containing structural units, amide group-containing structural units, and carboxyl group-containing structural units), and is preferably a structural unit consisting of only an alkyl structure. The alkyl structure is preferably a linear alkyl structure or a branched alkyl structure.

[0092] The alkyl structural unit preferably includes at least one type selected from the group consisting of structural units containing a linear alkyl structure and structural units containing a branched alkyl structure, and more preferably includes at least one type selected from the group consisting of structural units consisting only of a linear alkyl structure and structural units consisting only of a branched alkyl structure.

[0093] For example, when copolymer A is obtained via the above method (1a) or (1b), it is preferable that at least a hydrogenated conjugated diene monomer unit or an α-olefin monomer unit is introduced into copolymer A as a terminal group of copolymer A. The finally obtained copolymer A may contain these monomer units as alkyl structural units.

[0094] The alkanetriyl structural unit is a structural unit containing an alkanetriyl structure, and is preferably a structural unit consisting of only an alkanetriyl structure. The alkanetetrayl structural unit is a structural unit containing an alkanetetrayl structure, and is preferably a structural unit consisting of only an alkanetetrayl structure.

[0095] For example, when copolymer A is obtained through the above method (1a), the conjugated diene monomer unit may be introduced into the molecule of copolymer A as a monomer unit having no carbon-carbon double bond and having a branch point. In this case, the finally obtained copolymer A is a branched polymer, and may contain the conjugated diene monomer unit as an aliphatic hydrocarbon structural unit having a branch point, such as an alkanetriyl structural unit or an alkanetetrayl structural unit. When the aliphatic hydrocarbon structural unit contains a structural unit having a branch point, copolymer A is a branched polymer. The branched polymer may be a network polymer. Copolymer A containing a structural unit having a branch point can be three-dimensionally adsorbed to the dispersed material, and therefore can further improve dispersibility and stability.

[0096] Preferred embodiments of copolymer A include the following. Copolymer A in which the total content of the aliphatic hydrocarbon structural units and the nitrile group-containing structural units contained in copolymer A is 80% by mass or more and 100% by mass or less based on the mass of copolymer A. The total content is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more. Copolymer A in which the total content of the aliphatic hydrocarbon structural units, the nitrile group-containing structural units, and the amide group-containing structural units contained in copolymer A is 80% by mass or more and 100% by mass or less based on the mass of copolymer A. The total content is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more. Copolymer A in which the total content of the aliphatic hydrocarbon structural units, the nitrile group-containing structural units, the amide group-containing structural units, and the carboxyl group-containing structural units contained in copolymer A is 80% by mass or more and 100% by mass or less based on the mass of copolymer A. The total content is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more.

[0097] In this specification, the content of the structural unit can be determined by utilizing the amount of monomer used, NMR (nuclear magnetic resonance) and / or IR (infrared spectroscopy) measurement.

[0098] The copolymer A of the present invention has a Mooney viscosity (ML 1+4 ,100℃) is 10 to 70. It contains a nitrile group-containing monomer unit and an aliphatic hydrocarbon structural unit, and has a Mooney viscosity (ML 1+4 When the copolymer A having a Mooney viscosity (ML , 100° C.) of 10 to 70 is contained as a dispersant, the carbon fibers can be well dispersed when preparing a dispersion containing the carbon fibers as a conductive material. 1+4 ",100℃)" can be measured at a temperature of 100℃ in accordance with JIS K6300-1.

[0099] The Mooney viscosity of copolymer A must be 10 or more and 70 or less, preferably 60 or less, more preferably 55 or less, and even more preferably 50 or less. If the Mooney viscosity of copolymer A exceeds the above upper limit, the adsorption force of copolymer A to the carbon fiber surface is low, and carbon fibers with strong cohesive force cannot be dispersed, making it difficult to prepare a uniform conductive material dispersion. In addition, since the obtained conductive material dispersion has a high viscosity, metal foreign matter that is mixed in from the raw material cannot be efficiently removed by methods such as iron removal with a magnet, filtration, and centrifugation, and there is a risk of battery performance being reduced due to the remaining metal foreign matter.

[0100] The method for adjusting the Mooney viscosity of copolymer A is not particularly limited, but for example, the Mooney viscosity can be adjusted by changing the composition (e.g., structural unit type and content, hydrogenation rate), structure (e.g., linearity), molecular weight, preparation conditions (e.g., polymerization temperature, amount of molecular weight modifier) ​​of copolymer A. Specifically, the Mooney viscosity of copolymer A can be adjusted by the following methods. In method (5a), the amount of molecular weight modifier used in the preparation of copolymer A is increased to reduce the Mooney viscosity. In method (5b), a base is added to hydrolyze the nitrile group contained in the nitrile group-containing structural unit of copolymer A, thereby reducing the Mooney viscosity of copolymer A. In method (5c), a disperser that applies a larger shear force to copolymer A or a dispersant containing copolymer A is used to apply a mechanical shear force to reduce the Mooney viscosity.

[0101] Examples of molecular weight regulators that can be used in the above method (5a) include alkyl mercaptans such as octyl mercaptan, nonyl mercaptan, decyl mercaptan, dodecyl mercaptan, 3-mercapto-1,2-propanediol, etc., thioglycolic acid esters such as octyl thioglycolate, nonyl thioglycolate, 2-ethylhexyl thioglycolate, etc., 2,4-diphenyl-4-methyl-1-pentene, 1-methyl-4-isopropylidene-1-cyclohexene, α-pinene, β-pinene, etc.

[0102] In the above method (5b), a base may be added when preparing copolymer A containing nitrile group-containing monomer units and aliphatic hydrocarbon structural units, or a base may be added after dissolving an already prepared copolymer containing nitrile group-containing monomer units and aliphatic hydrocarbon structural units in a solvent capable of dissolving the copolymer. The base to be added may be at least one selected from the group consisting of inorganic bases and organic hydroxides (organic bases).

[0103] Examples of inorganic bases include chlorides, hydroxides, carbonates, nitrates, sulfates, phosphates, tungstates, vanadates, molybdates, niobates, or borates of alkali metals or alkaline earth metals; and ammonium hydroxide. Among these, hydroxides of alkali metals or alkaline earth metals are preferred from the viewpoint of easily supplying cations. Examples of hydroxides of alkali metals include lithium hydroxide, sodium hydroxide, potassium hydroxide, and the like. Examples of hydroxides of alkaline earth metals include calcium hydroxide, magnesium hydroxide, and the like. Among these, it is more preferable to use at least one selected from the group consisting of lithium hydroxide, sodium hydroxide, and potassium hydroxide. The metal contained in the inorganic base may be a transition metal.

[0104] The organic hydroxide is a salt containing an organic cation and a hydroxide ion. Examples of the organic hydroxide include trimethyl-2-hydroxyethyl ammonium hydroxide, tetramethyl ammonium hydroxide, cetyl trimethyl ammonium hydroxide, hexadecyl trimethyl ammonium hydroxide, trimethyl phenyl ammonium hydroxide, 3-trifluoromethyl-phenyl trimethyl ammonium hydroxide, and benzyl trimethyl ammonium hydroxide. Among these, it is particularly preferable to use at least one selected from the group consisting of trimethyl-2-hydroxyethyl ammonium hydroxide and tetramethyl ammonium hydroxide.

[0105] The amount of the base used is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more, based on the mass of copolymer A. The amount of the base used is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less, based on the mass of the copolymer. If the amount used is too small, the modification of the nitrile group by hydrolysis tends not to occur easily. If the amount used is too large, it may cause corrosion of the dispersion device and / or the inside of the battery.

[0106] In the method (5b), the modification of the nitrile group by hydrolysis can be carried out by mixing the copolymer A containing an aliphatic hydrocarbon structural unit and a nitrile group-containing monomer unit, a base, and a solvent. Any other components may be mixed. There is no limitation on the order of addition of the copolymer A, the base, and the solvent to the container and the mixing method, and they may be added to the container at the same time; the copolymer A, the base, and the solvent may be added separately to the container; or one or both of the copolymer A and the base may be mixed with the solvent to prepare a copolymer-containing liquid and / or a base-containing liquid, and the copolymer-containing liquid and / or the base-containing liquid may be added to the container. In particular, since the nitrile group can be efficiently modified, a method in which a base dispersion in which a base is dispersed in a solvent is added to a copolymer solution in which the copolymer A is dissolved in a solvent while stirring is preferred. A disperser (dispersing machine) or a homogenizer can be used for stirring. The solvent to be described later can be used.

[0107] There is no limitation on the temperature during mixing, but the denaturation can be accelerated by heating to 30°C or higher. In addition, a small amount of water and / or alcohol may be added to the container to promote the denaturation of copolymer A. Water and / or alcohol may be added to the container while mixing copolymer A and the base, or before adding copolymer A and the base to the container, or may be added to the container simultaneously with or subsequent to copolymer A and the base. In addition, when copolymer A, the base, and any optional components used as necessary are highly hygroscopic, water may be contained as absorbed water. The amount of water and / or alcohol is preferably 0.05 to 20% by mass, more preferably 0.05 to 5% by mass, and even more preferably 0.05 to 1% by mass, based on the mass of copolymer A.

[0108] Examples of alcohols include methanol, ethanol, propanol, isopropanol, butanol, isobutanol, secondary butanol, tertiary butanol, benzyl alcohol, ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, butylene glycol, hexanediol, pentanediol, glycerin, hexanetriol, and thiodiglycol. The alcohols can be used alone or in combination of two or more. The hydrolysis is preferably carried out in the presence of at least one selected from the group consisting of methanol, ethanol, and water, and is particularly preferably carried out in the presence of water.

[0109] The above method (5c) may be adjusted by applying a mechanical shearing force when preparing copolymer A containing nitrile group-containing monomer units and aliphatic hydrocarbon structural units, or by dissolving an already prepared copolymer containing nitrile group-containing monomer units and aliphatic hydrocarbon structural units in a solvent capable of dissolving the copolymer and then applying a mechanical shearing force. The Mooney viscosity can also be reduced by applying a mechanical shearing force to copolymer A before dissolution using a roll or kneader, but since copolymer A is used as a dispersant in a state where it is dissolved in a solvent capable of dissolving the copolymer, it is more preferable to apply a shearing force in the form of a copolymer solution.

[0110] Examples of the method of applying a shear force to the copolymer A in a solution state include a method using a dispersing means such as a homogenizer or a Silverson mixer. Although a shear force can be applied using a disperser or the like, it is preferable to use a dispersing means capable of applying a higher shear force such as a homogenizer or a Silverson mixer. Examples of the method of applying a mechanical shear force to the copolymer A before dissolution include a method using a dispersing means such as a kneader or a two-roll mill.

[0111] Preferred embodiments of the method for producing copolymer A include the following. A method for producing copolymer A, comprising: preparing a copolymer by polymerization reaction using a monomer composition containing a conjugated diene monomer and a nitrile group-containing monomer (methods (1a) and (2a)), and hydrogenating the conjugated diene monomer units contained in the copolymer (method (1a)). In this method, a part or all of the conjugated diene monomer units are hydrogenated. A method for producing copolymer A, comprising: preparing a copolymer by polymerization reaction using a monomer composition containing a conjugated diene monomer, a nitrile group-containing monomer, and an amide group-containing monomer (methods (1a), (2a) and (3a)), and hydrogenating the conjugated diene monomer units contained in the copolymer (method (1a)). In this method, a part or all of the conjugated diene monomer units are hydrogenated. A method for producing copolymer A, comprising: preparing a copolymer by polymerization reaction using a monomer composition containing a conjugated diene monomer and a nitrile group-containing monomer (methods (1a) and (2a)), hydrogenating the conjugated diene monomer units contained in the copolymer (method (1a)), and hydrolyzing the nitrile group-containing structural units contained in the copolymer by adding a base (method (5b)). In this method, a part or all of the conjugated diene monomer units are hydrogenated. Also, a part (but not all) of the nitrile group-containing structural units are hydrolyzed so that the nitrile group-containing structural units are contained in copolymer A. A method for producing copolymer A, comprising: preparing a copolymer by polymerization reaction using a monomer composition containing a conjugated diene monomer and a nitrile group-containing monomer (methods (1a) and (2a)), hydrogenating the conjugated diene monomer units contained in the copolymer (method (1a)), and applying a mechanical shear force to a copolymer solution (method (5c)). In this method, some or all of the conjugated diene monomer units are hydrogenated.

[0112] In the production method of the above aspect, the monomer composition may further contain an amide group-containing monomer and / or a carboxyl group-containing monomer.

[0113] The polymerization reaction used in the preparation of copolymer A is preferably an emulsion polymerization reaction, and a conventional emulsion polymerization method can be used. Polymerization agents such as emulsifiers (surfactants), polymerization initiators, chelating agents, oxygen scavengers, and molecular weight regulators used in emulsion polymerization can be any conventionally known agent, and are not particularly limited. For example, anionic emulsifiers or anionic and nonionic emulsifiers are usually used as emulsifiers.

[0114] Examples of the anionic emulsifier include fatty acid salts such as potassium tallow fatty acid, partially hydrogenated potassium tallow fatty acid, potassium oleate, and sodium oleate; resin acid salts such as potassium rosinate, sodium rosinate, potassium hydrogenated rosinate, and sodium hydrogenated rosinate; and alkylbenzene sulfonate salts such as sodium dodecylbenzene sulfonate. Examples of the nonionic emulsifier include emulsifiers of polyethylene glycol ester type, polypropylene glycol ester type, and block copolymer type of ethylene oxide and propylene oxide.

[0115] Examples of the polymerization initiator include thermal decomposition initiators such as persulfates, such as potassium persulfate and ammonium persulfate; organic peroxides, such as t-butyl hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, octanoyl peroxide, and 3,5,5-trimethylhexanoyl peroxide; azo compounds, such as azobisisobutyronitrile; and redox initiators consisting of these and a reducing agent, such as divalent iron ions. Among these, redox initiators are preferred. The amount of the initiator used is, for example, in the range of 0.01 to 10% by mass with respect to the total amount of the monomers.

[0116] The emulsion polymerization reaction may be either a continuous or batch type. The polymerization temperature may be either low-temperature or high-temperature polymerization, but is preferably 0 to 50°C, more preferably 0 to 35°C. The method of adding the monomer (lump addition, divided addition, etc.), the polymerization time, the polymerization conversion rate, etc. are not particularly limited. The conversion rate is preferably 85% by mass or more, more preferably 90% by mass or more.

[0117] The weight average molecular weight of copolymer A is preferably 5,000 or more, more preferably 10,000 or more, and even more preferably 50,000 or more. The weight average molecular weight of copolymer A is preferably 400,000 or less, more preferably 350,000 or less, and even more preferably 300,000 or less. When the weight average molecular weight of copolymer A is 5,000 or more and 400,000 or less, the adsorption to the dispersed material and the affinity to the dispersion medium become good, and the stability of the dispersion tends to be improved. The weight average molecular weight is a weight average molecular weight in terms of polystyrene, and can be measured by gel permeation chromatography (GPC). Specifically, it may be measured by the method described in the examples.

[0118] The dispersant contains at least copolymer A. The dispersant may further contain any polymer, any copolymer, etc. The content of copolymer A in the dispersant is preferably 50% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more. The content of copolymer A in the dispersant may be 100% by mass, in which case the dispersant consists of only copolymer A.

[0119] <Solvent> The solvent (dispersion medium) of the fibrous carbon dispersion is not particularly limited, but is preferably a high dielectric constant solvent, and preferably contains one of the high dielectric constant solvents or a mixed solvent of two or more of them. In addition, the high dielectric constant solvent may be mixed with one or more other solvents.

[0120] Examples of high dielectric constant solvents that can be used include amides (N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylcaprolactam, etc.), heterocyclics (cyclohexylpyrrolidone, 2-oxazolidone, 1,3-dimethyl-2-imidazolidinone, γ-butyrolactone, etc.), sulfoxides (dimethyl sulfoxide, etc.), sulfones (hexamethylphosphorotriamide, sulfolane, etc.), lower ketones (acetone, methyl ethyl ketone, etc.), carbonates (diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate, propylene carbonate, ethylene carbonate), water, and others such as tetrahydrofuran, urea, and acetonitrile. The dispersion medium preferably contains an amide-based organic solvent or water, and the amide-based organic solvent more preferably contains at least one selected from the group consisting of N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone. The relative dielectric constant of the high dielectric constant solvent can be a value listed in the Solvent Handbook, etc., and is preferably 2.5 or more at 20°C.

[0121] <Carbon fiber dispersion> The fibrous carbon dispersion contains fibrous carbon, a solvent (dispersion medium), and a dispersant. The fibrous carbon dispersion may contain optional components such as wetting agents, surfactants, pH adjusters, wetting penetrants, other additives such as leveling agents, other conductive materials, and other polymer components, as necessary, within a range that does not impair the object of the present invention. The optional components can be added at any timing, such as before preparing the dispersion, during dispersion, after dispersion, or a combination thereof.

[0122] The dispersibility of the fibrous carbon in the fibrous carbon dispersion can also be evaluated by the median diameter (μm) determined by a laser diffraction / scattering type particle size distribution analyzer. With the median diameter (μm) determined by a laser diffraction / scattering type particle size distribution analyzer, the particle diameter of the fibrous carbon aggregated particles can be estimated by the distribution of scattered light intensity by the particles. The median diameter (μm) is preferably 0.4 μm or more, and is preferably 5.0 μm or less, and more preferably 2.0 μm or less. By setting it within the above range, a fibrous carbon dispersion in an appropriate dispersion state can be obtained. If it is below the above range, fibrous carbon in an aggregated state will exist, and if it exceeds the above range, a large number of finely cut fibrous carbons will be generated, making it difficult to form an efficient conductive network. The median diameter can be measured by the method described in the examples.

[0123] The viscosity of the fibrous carbon dispersion, measured using a B-type viscometer at 25°C and 60 rpm, is preferably 10 mPa·s or more and less than 10,000 mPa·s, more preferably 10 mPa·s or more and less than 2,000 mPa·s, and even more preferably 10 mPa·s or more and less than 1,000 mPa·s.

[0124] The TI value of the fibrous carbon dispersion can be calculated by dividing the viscosity (mPa·s) at 6 rpm measured at 25°C with a B-type viscometer by the viscosity (mPa·s) at 60 rpm. The TI value is preferably 1.0 or more and less than 10.0, more preferably 1.0 or more and less than 5.0, and even more preferably 1.0 or more and less than 3.0. The higher the TI value, the greater the structural viscosity due to the entanglement of the fibrous carbon, dispersant, and other resin components, or the intermolecular forces thereof, and the lower the TI value, the smaller the structural viscosity. By setting the TI value within the above range, the entanglement of the fibrous carbon, dispersant, and other resin components can be suppressed while allowing these intermolecular forces to act appropriately.

[0125] The average fiber length of the fibrous carbon in the fibrous carbon dispersion is preferably 0.1 μm or more, more preferably 0.2 μm or more, and even more preferably 0.3 μm or more. Also, it is preferably 20 μm or less, and more preferably 10 μm or less. The average fiber length of the fibrous carbon in the fibrous carbon dispersion can be calculated by diluting the fibrous carbon dispersion 50 times with a non-aqueous solvent such as NMP, dropping the diluted fibrous carbon dispersion onto a substrate, drying the diluted fibrous carbon dispersion, observing the sample with a scanning electron microscope, and randomly selecting 300 pieces of fibrous carbon from the observation photograph and measuring the fiber length of each piece.

[0126] The content of the fibrous carbon is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and more preferably 0.8% by mass or more, based on the total amount of the fibrous carbon dispersion. Also, it is preferably 20% by mass or less, and more preferably 10% by mass or less. By setting it within the above range, the fibrous carbon can be present well and stably without causing sedimentation or gelation. It is more preferably 0.1 to 20% by mass, and even more preferably 0.5 to 10% by mass. Also, it is preferable that the content of the fibrous carbon is appropriately adjusted so that a fibrous carbon dispersion liquid with appropriate fluidity or viscosity is obtained depending on the specific surface area of ​​the fibrous carbon, affinity to the dispersion medium, dispersibility of the dispersant, etc.

[0127] The content of the dispersant is preferably 5 to 200 parts by mass, more preferably 10 to 100 parts by mass, and even more preferably 15 to 80 parts by mass, relative to 100 parts by mass of the fibrous carbon. The content of the dispersant is preferably 0.1 to 10% by mass, and more preferably 0.5 to 5% by mass, relative to the total amount of the fibrous carbon dispersion.

[0128] The solid content of the fibrous carbon dispersion is preferably from 0.2 to 40 mass %, more preferably from 0.5 to 20 mass %, and further preferably from 1 to 10 mass %.

[0129] The fibrous carbon dispersion may be prepared by separately preparing two or more kinds of fibrous carbon having different average outer diameters and adding them to a dispersion medium. When two or more kinds of fibrous carbon having different average outer diameters are used as the fibrous carbon, the average outer diameter of the first fibrous carbon is preferably 1 nm or more and less than 5 nm. The average outer diameter of the second fibrous carbon is preferably 5 nm or more and 30 nm or less, more preferably 20 nm or less. When two or more kinds of fibrous carbon having different average outer diameters are used as the fibrous carbon, the mass ratio of the first fibrous carbon to the second fibrous carbon is preferably 1:10 to 1:100, more preferably 1:10 to 1:50.

[0130] The dispersibility of fibrous carbon in the fibrous carbon dispersion can be evaluated by the phase angle and complex modulus of elasticity measured by dynamic viscoelasticity measurement. The phase angle means the phase shift of the stress wave when the strain applied to the fibrous carbon dispersion is a sine wave. If it is a pure elastic body, the phase angle will be 0° because it will be a sine wave in phase with the applied strain. On the other hand, if it is a pure viscous body, the stress wave will be advanced by 90°. In a typical viscoelasticity measurement sample, the phase angle will be a sine wave greater than 0° and less than 90°, and if the dispersibility of fibrous carbon in the fibrous carbon dispersion is good, the phase angle will approach 90° for a pure viscous body. In addition, the complex modulus of elasticity of the fibrous carbon dispersion becomes smaller as the dispersibility of the fibrous carbon is good and the viscosity of the fibrous carbon dispersion becomes lower.

[0131] The phase angle and complex modulus measured by dynamic viscoelasticity measurement depend on the concentration of fibrous carbon in the dispersion. When carbon fibers (such as CNTs) with a high specific surface area are used as the fibrous carbon, the lower the content of fibrous carbon containing carbon fibers, the closer the resulting dispersion is to a pure viscous body, and the closer the phase angle is to 90°. Conversely, it is difficult to uniformly disperse a dispersion containing a high concentration of fibrous carbon containing carbon fibers, and the phase angle of the resulting dispersion is less than 19°. In the present invention, since copolymer A can achieve both good dispersibility and stability, a fibrous carbon dispersion having a phase angle of 19° or more at a frequency of 1 Hz can be obtained even when the concentration of fibrous carbon is high.

[0132] The fibrous carbon dispersion of the present invention has a phase angle at a frequency of 1 Hz measured by dynamic viscoelasticity measurement of 19° or more, more preferably 30° or more, and even more preferably 45° or more. The phase angle at a frequency of 1 Hz is preferably 90° or less, more preferably 85° or less, and even more preferably 80° or less. The complex modulus of the fibrous carbon dispersion of the present invention measured by dynamic viscoelasticity measurement is preferably less than 20 Pa, more preferably 10 Pa or less, and even more preferably 5 Pa or less. The complex modulus of the fibrous carbon dispersion is preferably 0.01 Pa or more, more preferably 0.05 Pa or more, and even more preferably 0.1 Pa or more. The complex modulus and phase angle can be measured by the method described in the examples.

[0133] The complex modulus of the fibrous carbon dispersion of the present invention is small because the agglomerations of the carbon fibers are loosened by the effect of the dispersant containing copolymer A. In the fibrous carbon dispersion of this embodiment, it is preferable that the carbon fiber concentration x (mass%) in the fibrous carbon dispersion and the complex modulus y (Pa) of the fibrous carbon dispersion measured by dynamic viscoelasticity measurement satisfy the relationships of the following formulas (1), (2), and (3): y<8x(1) y<20(2) 0.1≦x≦10(3)

[0134] That is, from the above formulas (1) and (2), it is preferable that the complex modulus y of the fibrous carbon dispersion measured by dynamic viscoelasticity measurement is less than 20 Pa and that y<8x is satisfied. Also, from the above formula (3), it is preferable that the carbon fiber concentration x (mass%) is in the range of 0.1≦x≦10.

[0135] As mentioned above, the dispersibility of fibrous carbon can be judged by complex modulus and phase angle, so that the preferred embodiment of the method for producing conductive dispersion includes the following method for producing I and II. By this method for producing, the fibrous carbon dispersion that can achieve both good dispersibility and stability can be obtained. (Step I) A step of mixing fibrous carbon containing carbon fibers, a dispersant containing copolymer A, and a dispersion medium. (Step II) A step of performing a dispersion treatment after Step I to obtain a dispersion in which the rheometer measurement results show a phase angle of 19° or more at a frequency of 1 Hz and a complex modulus of elasticity of less than 20 Pa.

[0136] The average fiber length of the fibrous carbon is preferably 0.5 μm or more, more preferably 0.8 μm or more, and even more preferably 1.0 μm or more. Also, it is preferably 20 μm or less, and more preferably 10 μm or less. The average fiber length of the fibrous carbon can be calculated by first observing and photographing the fibrous carbon with a scanning electron microscope, randomly selecting 300 pieces of fibrous carbon from the observation photograph, and measuring the fiber length of each piece.

[0137] The aspect ratio is the fiber length of the fibrous carbon divided by the outer diameter. A representative aspect ratio can be calculated using the average fiber length and the average outer diameter. The higher the aspect ratio of the fibrous carbon, the higher the electrical conductivity can be obtained when an electrode is formed. The aspect ratio of the fibrous carbon is preferably 30 or more, more preferably 50 or more, and even more preferably 80 or more. In addition, it is preferably 10,000 or less, more preferably 3,000 or less, and even more preferably 1,000 or less.

[0138] The specific surface area of ​​fibrous carbon is 100m 2 / g or more, and 150m 2 / g or more is more preferable, and 200m 2 / g or more is more preferable. 2 / g or less, and 2 / g or less is more preferable. The specific surface area of ​​the fibrous carbon is calculated by the BET method using nitrogen adsorption measurement. When the average outer diameter, average fiber length, aspect ratio, and specific surface area of ​​the fibrous carbon are within the above ranges, a conductive path developed in the electrode is easily formed.

[0139] The carbon purity of the fibrous carbon is represented by the content (mass%) of carbon atoms in the fibrous carbon, and is preferably 80 mass% or more relative to 100 mass% of the fibrous carbon.

[0140] For the purpose of removing or reducing impurities such as metal catalysts and increasing the carbon purity, fibrous carbon that has been subjected to a purification treatment may be used.

[0141] When fibrous carbon is dispersed in a disperser by collision with media such as a bead mill, or when it is repeatedly passed through a disperser over a long period of time, the fibrous carbon may be broken and short-flaked carbonaceous matter may be generated. When short-flaked carbonaceous matter is generated, the viscosity of the fibrous carbon dispersion decreases, and the gloss of the coating film obtained by coating and drying the fibrous carbon dispersion increases. Judging from these evaluation results alone, however, the short-flaked carbonaceous matter has high contact resistance and is difficult to form a conductive network, which may worsen the resistance of the electrode. The degree of short-flaked carbonaceous matter generation can be confirmed by diluting the dispersion liquid, dropping it onto a substrate with a smooth surface and good affinity with the dispersion medium, and drying the sample, and observing it with a scanning electron microscope. By adjusting the dispersion conditions and the composition of the dispersion liquid so that carbonaceous matter of 0.1 μm or less is not generated, an electrode with high conductivity can be obtained.

[0142] The fibrous carbon may be produced by any method. The fibrous carbon can generally be produced by, but is not limited to, a laser ablation method, an arc discharge method, a thermal CVD method, a plasma CVD method, and a combustion method. For example, the fibrous carbon can be produced by contacting a carbon source with a catalyst at 500 to 1000°C in an atmosphere with an oxygen concentration of 1% by volume or less. The carbon source may be at least one of a hydrocarbon and an alcohol.

[0143] <Drying process> The method for removing the solvent and drying is not particularly limited as long as it can remove the solvent from the non-slurry mixture, and examples of the method include drying methods such as hot air drying, vacuum drying, freeze drying, etc. Among these, hot air drying and vacuum drying are preferred from the viewpoint of productivity.

[0144] <Composite for secondary battery electrodes> The composite for a secondary battery electrode contains an electrode active material, fibrous carbon, and may further contain an optional binder resin. The composite for an electrode may further contain optional components.

[0145] The fibrous carbon contained in the electrode composite of the present invention is at least partially crushed and adheres to the surface of the active material.

[0146] The presence of fibrous carbon in a crushed form on the surface of the active material can efficiently supply electrons required for the battery reaction to the active material, and can also contribute to reducing the contact resistance between active materials when an electrode is fabricated. Therefore, when the fibrous carbon is crushed and uniformly adsorbed on the surface of the active material to form an electrode for a secondary battery, the electrode resistance is reduced, and the formation of an electronic conduction path to the active material during the battery reaction is favored, thereby improving the battery rate characteristics and cycle characteristics. In addition, since an efficient conductive path can be formed with a small amount of conductive additive, the amount of conductive additive in the electrode can be reduced, and the battery capacity can be improved.

[0147] The crushed form of fibrous carbon refers to a form in which secondary particles (aggregates) of fibrous carbon are broken down into primary particles or a bundle state in which multiple primary particles are bundled together. The state in which fibrous carbon is crushed and adsorbed onto the active material surface includes a state in which the primary particles and / or bundles are isolated, and a state in which the primary particles and / or bundles are overlapped. From the viewpoint of electron supply to the active material and conductive paths between composites, a state in which the primary particles and / or bundles are overlapped and adsorbed in a mesh-like shape is preferred.

[0148] In the present invention, the state in which the fibrous carbon is adsorbed on the surface of the active material in a crushed form means that the area of ​​the fibrous carbon adsorbed on the active material in a crushed fiber state is 10% or more of the entire surface of the active material, preferably 20% or more, and more preferably 50% or more.

[0149] The area occupied by the fibrous carbon adsorbed to the active material in the crushed fiber state can be measured from the contrast difference between the active material and the fibrous carbon in images taken at magnifications of 5,000 to 50,000 times using a scanning electron microscope (SEM) or a scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX), and the average value of the above areas calculated from 20 pieces of active material in the composite was used.

[0150] When the combustion temperature of the fibrous carbon in an oxygen-containing atmosphere is 520° C. or lower, the electrode composite of the present invention becomes a composite in a homogeneous state in which the fibrous carbon adsorbed on the active material surface is loosened.

[0151] The temperature of the exothermic peak in the present invention can be determined by TG-DTA (Thermogravimetry-Differential Thermal Analysis) measurement. Specifically, a TG curve and a DTA curve are obtained by performing TG-DTA measurement under air or oxygen flow conditions. In the obtained DTA curve, the top of the maximum exothermic peak resulting from the combustion of the fibrous carbon, which is located in the vicinity of 300 to 700°C, is read and determined as the temperature of the exothermic peak of the fibrous carbon. This represents the combustion temperature of the fibrous carbon. Generally, fibrous carbon has thick bundles in which primary particles are strongly aggregated by van der Waals forces, and large secondary aggregates in which bundles are aggregated together. The physical properties, such as thermal stability, differ depending on the state of aggregation. Therefore, even for the same type of fibrous carbon, the combustion temperature changes depending on the state of aggregation, and the stronger the aggregation, the higher the combustion temperature.

[0152] The combustion temperature of the fibrous carbon in the secondary battery electrode composite in an oxygen-containing atmosphere is preferably 520°C or less, since the fibrous carbon on the active material is adsorbed in a more loose state, which favors the formation of an electron conduction path from the fibrous carbon to the active material and improves the battery characteristics. It is preferably 480°C or less, and more preferably 450°C or less.

[0153] When the volume resistivity of the electrode composite for secondary batteries is 500 Ω·cm or less under a load of 20 kN, the fibrous carbon in the composite is not unevenly distributed and is adsorbed on the active material in a more uniform state, which reduces the electrode resistance when used as a secondary battery electrode. A volume resistivity of 100 Ω·cm or less is preferable, and 50 Ω·cm or less is more preferable.

[0154] The volume resistivity of the electrode composite for secondary batteries can be determined by performing resistivity measurement based on the four-terminal four-probe method. Specifically, four needle-like probes (electrodes) are brought into contact with the composite for secondary battery electrodes to be measured, and the resistance of the test piece is calculated from the current flowing between the two outer probes and the potential difference generated between the two inner probes. The volume resistivity of the CNTs can then be calculated from the measured resistance and the thickness of the test piece. The measurement is performed using a volume resistivity measuring device (for example, the low-resistance version of the automatic powder resistivity measuring system MCP-PD600 manufactured by Nitto Seiko Analytech Co., Ltd.) under a load of 20 kN.

[0155] The secondary battery electrode composite is preferably in the form of particles, and the average particle size is preferably from 0.5 μm to 500 μm, more preferably from 1 μm to 200 μm.

[0156] As mentioned above, when the combustion temperature is 520°C or less and the volume resistivity is 100 Ω·cm or less, the fibrous carbon in the composite is crushed and is thin and uniformly adsorbed on the active material, which is preferable because when used as an electrode for a secondary battery, it reduces the electrode resistance and is favorable for the formation of an electronic conduction path to the active material during the battery reaction, improving the battery rate characteristics and cycle characteristics. In addition, because an efficient conductive path can be formed with a small amount of conductive additive, the amount of conductive additive in the electrode can be reduced, making it possible to improve the battery capacity.

[0157] The content of fibrous carbon in the composite is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, and even more preferably 0.05% by mass or more, based on the mass of the composite for secondary battery electrodes. Also, it is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less. If it exceeds the above range, the amount of active material filled in the electrode decreases, resulting in a decrease in battery capacity. In particular, for high-capacity batteries, 10% by mass or less is preferable. If it is below the above range, the conductivity of the electrode and battery may be insufficient.

[0158] The composite may contain a conductive material other than fibrous carbon. Examples of the other conductive material include carbon materials such as carbon black, fullerene, graphene, multilayer graphene, and graphite. The carbon black may be neutral, acidic, or basic, and may be oxidized carbon black or graphitized carbon black. The other conductive materials may be used alone or in combination of two or more.

[0159] <Binder resin> The composite of the present invention may contain a binder resin as necessary. The binder resin is not particularly limited as long as it is normally used as a binder resin, and can be appropriately selected according to the purpose. The binder resin used in the composite is preferably a resin capable of binding between substances such as active materials and fibrous carbon. Examples of the binder resin used in the composite include polymers or copolymers containing ethylene, propylene, vinyl chloride, vinyl acetate, maleic acid, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, styrene, etc. as structural units; polyurethane resins, polyester resins, phenolic resins, epoxy resins, phenoxy resins, urea resins, melamine resins, alkyd resins, acrylic resins, formaldehyde resins, silicone resins, and fluororesins; cellulose-based resins such as carboxymethylcellulose; elastomers such as styrene-butadiene rubber and fluororubber; and conductive resins such as polyaniline and polyacetylene. Modified bodies, mixtures, and copolymers of these resins may also be used. Particularly, fluororesins are preferred, such as polytetrafluoroethylene (PTFE), polyvinyl fluoride (PVF), polyvinylidene fluoride (PVDF), and modified products thereof. These may be used alone or in combination of two or more. Among these, from the standpoint of resistance, polymers or copolymers having fluorine atoms in the molecule, such as polyvinylidene fluoride, polyvinyl fluoride, tetrafluoroethylene, resins having these structural units, and modified products thereof are preferred.

[0160] The content of the binder resin in the composite is preferably 0.1% by mass or more, and more preferably 0.3% by mass or more, based on the mass of the active material (the mass of the active material being 100% by mass), and is preferably 20% by mass or less, and more preferably 10% by mass or less.

[0161] <Electrode for secondary batteries> The secondary battery electrode of the present invention includes a composite for a secondary battery electrode. The electrode may further include optional components such as a binder and a dispersant. In general, the electrode is formed by powder compression molding or by applying a composite slurry onto a current collector and removing volatiles.

[0162] The material and shape of the current collector are not particularly limited, and can be appropriately selected from those suitable for various secondary batteries. For example, the material of the current collector can be metals or alloys such as aluminum, copper, nickel, titanium, or stainless steel. In addition, as for the shape, a flat foil is generally used, but a current collector with a roughened surface, a perforated foil, or a mesh-shaped current collector can also be used. The thickness of the current collector is preferably about 0.5 to 30 μm.

[0163] <Method of manufacturing secondary battery electrodes> A secondary battery electrode can be formed by adding a binder or the like to a composite for a secondary battery electrode, forming each component into a sheet by pressing or the like under dry conditions that do not contain solvents, and then powder pressure molding the sheet, or by preparing a composite slurry, coating it on a current collector, and removing the volatile components. The powder pressure molding method without using a composite slurry is preferable because it can reduce the energy consumption required for drying the solvent.

[0164] The method for powder compression molding is not particularly limited, and any known method can be used. When an electrode is produced by powder pressure molding without using a composite material slurry, a dry mixture in which the electrode composite and a binder are mixed in advance, or a dried product after wet mixing may be used. The method for adding a binder or the like to the secondary battery electrode composite and dry-mixing or wet-mixing each component is not particularly limited, and various dispersing machines, mixers, granulators, etc. can be appropriately selected.

[0165] When forming an electrode by adding a binder or the like to a composite for a secondary battery electrode by powder pressure molding and forming each component into a sheet by pressing or the like, each component obtained by adding a binder or the like to a composite for a secondary battery electrode, or a dried product of the dry mixture or wet mixture, may be directly supplied to a current collector and pressure molded, or a free-standing film made of each component obtained by adding a binder or the like to a composite for a secondary battery electrode, or a dried product of the dry mixture or wet mixture, may be prepared in advance and then laminated on a current collector. Also, a thin resin film serving as a binder component may be formed in advance on a current collector.

[0166] Examples of the method for powder pressure molding include a planographic press, a calendar roll, etc. Among them, the use of a calendar roll is preferred because of its productivity and ability to produce uniform molding.

[0167] The method for producing an electrode using the composite slurry is not particularly limited, and a known method can be used.Specific examples include die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic painting.As a drying method after coating, standing drying, a blower dryer, a hot air dryer, an infrared heater, a far infrared heater, and the like can be used, but are not particularly limited thereto.

[0168] After the composite slurry is applied, it may be rolled using a lithographic press, a calendar roll, etc. The thickness of the electrode film is, for example, 1 μm or more and 500 μm or less, and preferably 10 μm or more and 300 μm or less.

[0169] <Secondary battery> The secondary battery includes a positive electrode, a negative electrode, and an electrolyte, and at least one selected from the group consisting of the positive electrode and the negative electrode includes an electrode film made from the composite of the present invention.

[0170] The positive electrode may be an electrode film containing a positive electrode active material formed on a current collector, and the negative electrode may be an electrode film containing a negative electrode active material formed on a current collector.

[0171] The electrolyte may be any of a liquid electrolyte, a gel electrolyte, and a solid electrolyte. For example, the liquid electrolyte may contain an electrolyte salt such as a lithium salt and a non-aqueous solvent. As the electrolyte salt, various conventionally known electrolytes capable of moving ions can be used. For example, lithium salts such as LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, Li(CF3SO2)3C, LiI, LiBr, LiCl, LiAlCl, LiHF2, LiSCN, or LiBPh4 (wherein Ph is a phenyl group) can be used, but are not limited thereto. The electrolyte salt is preferably dissolved in a non-aqueous solvent and used as an electrolytic solution.

[0172] The non-aqueous solvent is not particularly limited, but examples thereof include carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octanoic lactone; glymes such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and sulfolane; and nitriles such as acetonitrile. These solvents may be used alone or in combination of two or more.

[0173] The secondary battery preferably includes a separator, such as, but not limited to, polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and nonwoven fabrics obtained by subjecting these to hydrophilic treatment.

[0174] The structure of the secondary battery is not particularly limited, but typically includes a positive electrode and a negative electrode, and a separator that is provided as necessary, and can be in various shapes depending on the purpose of use, such as a paper type, a cylindrical type, a button type, or a laminated type.

[0175] The composite for secondary battery electrodes of the present invention is an ideal composite of active material and fibrous carbon, and therefore can be suitably used not only for electrodes made from composite slurries, but also for electrodes made by solid or semi-solid processes. Electrodes made by these solid processes can be applied not only to lithium ion secondary batteries using conventional electrolytes, but also to all-solid batteries and semi-solid batteries.

[0176] The secondary battery of the present invention can be suitably used as a battery for vehicles such as automobiles, and portable electronic devices such as personal computers and smartphones. EXAMPLES

[0177] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples as long as it does not exceed the gist of the present invention. Unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass". In the examples, a "dispersant-containing liquid" containing a "dispersant" and a solvent may be referred to as a "dispersant solution".

[0178] <Measurement of weight average molecular weight (Mw) of copolymer> The weight average molecular weight (Mw) of the copolymer was measured by gel permeation chromatography (GPC) equipped with an RI detector. The apparatus used was HLC-8320GPC (manufactured by Tosoh Corporation), and three separation columns were connected in series. The packing materials were "TSK-GELSUPERAW-4000", "AW-3000", and "AW-2500" manufactured by Tosoh Corporation, respectively. The oven temperature was 40°C, and an N,N-dimethylformamide solution of 30 mM triethylamine and 10 mM LiBr was used as the eluent, and the measurement was performed at a flow rate of 0.6 mL / min. The concentration of the measurement sample was adjusted to 1% using a solvent consisting of the eluent, and 20 microliters were injected. The weight average molecular weight is a polystyrene equivalent value.

[0179] <Measurement of hydrogenation rate of copolymer> The hydrogenation rate was determined by IR measurement in the same manner as the infrared spectroscopy analysis by the total reflection measurement method described above. The double bond derived from the conjugated diene monomer unit has a peak at 970 cm-1, and the hydrogenated single bond has a peak at 723 cm-1. The hydrogenation rate was calculated from the ratio of the heights of these two peaks.

[0180] <Mooney viscosity of copolymer (ML 1+4 , 100℃) The Mooney viscosity of copolymer A is measured by preparing a measurement sample from a copolymer solution containing a solvent capable of dissolving it. When it is dissolved in NMP, the NMP solution of copolymer A is coagulated with water, washed with methanol, and vacuum dried at a temperature of 60°C for 12 hours to prepare a measurement sample. The Mooney viscosity (ML) of 40 g of the measurement sample is measured using an L-type rotor at a temperature of 100°C in accordance with the Japanese Industrial Standard JISK6300-1. 1+4 , 100℃) were measured.

[0181] <Measurement of initial viscosity of fibrous carbon dispersion> The viscosity value was measured using a B-type viscometer ("BL" manufactured by Toki Sangyo Co., Ltd.) at a temperature of 25°C. After thoroughly stirring the fibrous carbon dispersion with a spatula, the viscosity value was immediately measured at a rotation speed of the B-type viscometer rotor of 60 rpm. The rotors used for the measurements were No. 1 when the viscosity value was less than 100 mPa·s, No. 2 when the viscosity value was 100 or more and less than 500 mPa·s, No. 3 when the viscosity value was 500 or more and less than 2,000 mPa·s, and No. 4 when the viscosity value was 2,000 or more and less than 10,000 mPa·s. The lower the viscosity, the better the dispersibility, and the higher the viscosity, the worse the dispersibility. The obtained fibrous carbon dispersion in which it was clearly separated or settled was judged to have poor dispersibility. Judgment criteria ◎: Less than 500 mPa·s (Excellent) ○: 500 mPa·s or more but less than 2,000 mPa·s (Good) △: 2,000 mPa·s or more but less than 10,000 mPa·s (Acceptable) ×: 10,000 mPa·s or more, settling or separation (Poor)

[0182] <Measurement of complex modulus and phase angle of fibrous carbon dispersion> The complex modulus and phase angle of the fibrous carbon dispersion were evaluated by performing dynamic viscoelasticity measurements at 25°C, a frequency of 1Hz, and a strain rate range of 0.01% to 5% using a rheometer (RheoStress1 rotational rheometer manufactured by ThermoFisherScientific Co., Ltd.) with a cone of 60mm diameter and 2°. The larger the obtained phase angle, the better the dispersibility, and the smaller the phase angle, the worse the dispersibility. In addition, the smaller the obtained complex modulus, the better the dispersibility, and the larger the complex modulus, the worse the dispersibility. Phase angle judgment criteria ◎: 45° or more (excellent) ○: 30° or more and less than 45° (good) △: 19° or more and less than 30° (acceptable) ×: Less than 19° (bad) Complex modulus criteria ◎: Less than 5Pa (Excellent) ○: 5 Pa or more but less than 20 Pa (OK) ×: 20 Pa or more but less than 100 Pa (bad) ××: 100 Pa or more (extremely poor)

[0183] <Preparation of Copolymer 1> In a stainless steel polymerization reactor, 30 parts of acrylonitrile, 70 parts of 1,3-butadiene, 3 parts of potassium soap oleate, 0.3 parts of azobisisobutyronitrile, 0.55 parts of t-dodecyl mercaptan, and 200 parts of ion-exchanged water were added. Under a nitrogen atmosphere, polymerization was carried out at 45°C for 20 hours while stirring, and the polymerization was terminated at a conversion rate of 90%. Unreacted monomers were removed by vacuum stripping to obtain an acrylonitrile-conjugated diene rubber latex with a solid content concentration of about 30%. Subsequently, ion-exchanged water was added to the latex to adjust the total solid content concentration to 12%, and the latex was placed in a 1L autoclave equipped with a stirrer, and nitrogen gas was passed through it for 10 minutes to remove dissolved oxygen in the contents. A catalyst solution prepared by dissolving 75 mg of palladium acetate as a hydrogenation catalyst in 180 mL of ion-exchanged water to which nitric acid was added in an amount four times the moles of palladium was added was added to the autoclave. After replacing the inside of the autoclave with hydrogen gas twice, the contents of the autoclave were heated to 50°C while pressurizing with hydrogen gas up to 3 MPa, and hydrogenation reaction was carried out for 6 hours. Thereafter, the contents were returned to room temperature, the inside of the autoclave was made into a nitrogen atmosphere, and the solid content was dried to recover copolymer 1. The hydrogenation rate of copolymer 1 was 99.5%, and the weight average molecular weight (Mw) was 150,000. In the acrylonitrile-conjugated diene rubber, the content of the conjugated diene monomer unit was 70% and the content of the nitrile group-containing monomer unit was 30% based on the mass of the acrylonitrile-conjugated diene rubber. In addition, in copolymer 1, the content of the aliphatic hydrocarbon structural unit containing an alkylene structural unit was 70%, and the content of the nitrile group-containing monomer unit was 30% based on the mass of copolymer 1. The content of these monomer units and the content of the structural units were determined from the amount of monomer used (hereinafter the same).

[0184] <Synthesis Example 1: Preparation of Dispersant 1> 9 parts of copolymer 1 and 91 parts of NMP were placed in a stainless steel container 1 and stirred for 1 hour with a disperser to obtain a dispersant 1-containing liquid containing copolymer 1 and NMP as dispersant 1. The Mooney viscosity (ML 1+4, 100°C) was measured and found to be 50. In Dispersant 1, the content of aliphatic hydrocarbon structural units was 70%, and the content of nitrile group-containing monomer units was 30%, based on the mass of Dispersant 1. The contents of these structural units were determined using the amounts of monomers used, NMR (nuclear magnetic resonance) and / or IR (infrared spectroscopy) measurements (the same applies below).

[0185] <Preparation of Copolymer 2> Copolymer 2 was obtained in the same manner as copolymer 1, except that the content of t-dodecyl mercaptan, a molecular weight regulator, was changed to 0.35 parts. The hydrogenation rate of copolymer 2 was 99.2%, and the weight average molecular weight (Mw) was 180,000. In copolymer 2, the content of aliphatic hydrocarbon structural units including alkylene structural units was 70%, and the content of nitrile group-containing monomer units was 30%, based on the mass of copolymer 2.

[0186] <Synthesis Example 2: Preparation of Dispersant 2> 16 parts of NaOH and 84 parts of NMP were placed in a stainless steel container 1 and stirred with a disperser for 1 hour to prepare a NaOH suspension. 9 parts of copolymer 2 and 91 parts of NMP were placed in a stainless steel container 2 and stirred with a disperser for 1 hour to prepare a solution of copolymer 2. Next, the NaOH suspension and the solution of copolymer 2 were placed in a stainless steel container 3 so that NaOH and copolymer 2 had the composition shown in Table 1, and NMP was further added to adjust the concentration. Stirring was performed for 2 hours with a disperser to obtain a dispersant 2-containing liquid containing copolymer 2, dispersant 2 containing NaOH, and dispersant 2 containing NMP. The Mooney viscosity (ML 1+4 , 100°C) was measured and found to be 42.

[0187] <Preparation of Copolymer 3> Copolymer 3 was obtained in the same manner as copolymer 1, except that the content of t-dodecyl mercaptan, a molecular weight regulator, was changed to 0.25 parts. The hydrogenation rate of copolymer 3 was 99.1%, and the weight average molecular weight (Mw) was 230,000. In copolymer 3, the content of aliphatic hydrocarbon structural units including alkylene structural units was 70%, and the content of nitrile group-containing monomer units was 30%, based on the mass of copolymer 3.

[0188] <Synthesis Example 3: Preparation of Dispersant 3> A dispersant 3-containing liquid containing copolymer 3 and NMP as dispersant 3 was obtained in the same manner as in Synthesis Example 1, except that the dispersing machine used was changed to a homogenizer and a shear force was applied to the solution. The Mooney viscosity (ML 1+4 , 100°C) was measured and found to be 55.

[0189] The abbreviations in the columns for monomer and molecular weight modifier in Table 1 have the following meanings: BD: 1,3-butadiene, MBD: 2-methyl-1,3-butadiene, AN: acrylonitrile, AAm: acrylamide, BA: butyl acrylate, TDM: t-dodecyl mercaptan.

[0190] <Preparation of Copolymers 4 to 9, Synthesis Examples 4 to 9, and Dispersants 4 to 9> The monomer composition, the amount of base, and the presence or absence of shear treatment during preparation were changed according to Table 1, and copolymers 4 to 9 were prepared with reference to copolymers 1 to 3, respectively, and dispersant 4 to 9-containing solutions were obtained with reference to synthesis examples 1 to 3. The Mooney viscosity of each dispersant was as shown in Table 1.

[0191] <Synthesis Example 10: Preparation of Dispersant 10> H-NBR1 (H-NBR (hydrogenated acrylonitrile-butadiene rubber) Therban® 3406 manufactured by ARLANXEO, acrylonitrile content 34%) and NMP were added to a stainless steel container 1 and dissolved with a disperser. A high shear force was applied to the H-NBR1 solution using a homogenizer to obtain a liquid containing dispersant 10. The Mooney viscosity (ML 1+4, 100℃) was measured and found to be 50.

[0192] <Synthesis Example 12: Preparation of Dispersant 12> The NaOH suspension and H-NBR2 solution prepared in the same manner as in Production Example 2 were placed in a stainless steel container 1 so that the NaOH and H-NBR2 (H-NBR (hydrogenated acrylonitrile-butadiene rubber) Zetpol(R) 2000L manufactured by Zeon Corporation, acrylonitrile content 36.2%) had the composition shown in Table 1, and NMP was further added to adjust the concentration. The solution was stirred with a homogenizer for 2 hours to apply a high shear force to the solution, and a dispersant 12 containing H-NBR2 and NaOH, and a dispersant 12-containing liquid containing NMP were obtained. The Mooney viscosity (ML 1+4 , 100℃) was measured and found to be 48.

[0193] <Synthesis Examples 11 and 13: Preparation of Dispersants 11 and 13> The type and amount of the base used were changed according to Table 1, and solutions containing Dispersants 11 and 13 were obtained with reference to Synthesis Examples 10 and 12, respectively. The Mooney viscosity of each dispersant was as shown in Table 1.

[0194] [Table 1]

[0195] Although the order and method of mixing the base and the copolymer are not limited to those described in the examples, it is preferable to disperse (or dissolve) the base in a solvent in advance and add it to the copolymer solution, since the contact efficiency between the base and the copolymer is high, and hydrolysis is likely to proceed easily. This is also effective in stabilizing quality control and shortening production time.

[0196] <Preparation of fibrous carbon dispersion> <Production Example 1> According to the composition shown in Table 2, a dispersant-containing liquid containing a dispersant, NMP, and, if specified, a base, or a dispersant was added to a stainless steel container, and NMP was added to adjust the concentration, and the mixture was stirred with a disperser until it became uniform. Then, the conductive material was added while stirring with a disperser, and a square-hole high shear screen was attached to a high shear mixer (L5M-A, manufactured by SILVERSON). The mixture was dispersed at a speed of 8,500 rpm until the entire mixture became uniform and the dispersion particle size was 250 μm or less as measured by a grind gauge. Next, the liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a 25-pass dispersion process was performed. The dispersion process was performed using a single nozzle chamber with a nozzle diameter of 0.25 mm and a pressure of 100 MPa. The mixture was then passed through a nylon mesh with 48 μm openings three times, and filtered through a magnetic filter (manufactured by Tok Engineering) at room temperature and a magnetic flux density of 12,000 Gauss to obtain a conductive material dispersion (Dispersion 1). After filtration, magnetic granular metal pieces were found to adhere to the magnetic filter.

[0197] (Examples 2 to 13) According to the composition shown in Table 2, each dispersion (Dispersions 2 to 13) was obtained in the same manner as in Production Example 1. All of the fibrous carbon dispersions (Dispersions 2 to 13) of Production Examples 2 to 13 had low viscosity and good stability.

[0198] The abbreviations in Table 2 have the following meanings: ·NTP3003: NTP3003 (Shenzhen NanotechPort Co. Ltd., multi-walled CNT, outer diameter 7~15nm)

[0199] [Table 2]

[0200] As shown in Table 2, all of the fibrous carbon dispersions of Production Examples 1 to 13 (Dispersions 1 to 13) had low viscosity and good dispersion. In particular, the Mooney viscosity (ML 1+4Dispersions with a measured viscosity (at 100° C.) of 40 or more and 50 or less had extremely low viscosity. Similarly, the complex modulus and phase angle of Dispersions 1 to 13 were all good.

[0201] The dispersant (copolymer A) of Production Examples 1 to 13 has a Mooney viscosity of 70 or less, which is higher than that of ordinary nitrile rubber having a high Mooney viscosity, and is therefore believed to have improved adsorption power to fibrous carbon, making it easier to obtain fibrous carbon dispersions with good dispersibility. In addition, if the Mooney viscosity of the nitrile rubber is less than 10, it is believed that the copolymer has low adsorption stability to the conductive material and cannot disperse carbon fibers with strong cohesion at a high concentration. In other words, it is believed that by including a copolymer with a Mooney viscosity of 10 or more and 70 or less as a dispersant, it is possible not only to suppress the aggregation of carbon fibers and to create a good dispersion state, but also to achieve both dispersibility and stability even when dispersed at a high concentration.

[0202] <Electrode composite for secondary batteries> (Example 1-1) According to the composition shown in Table 3, an electrode composite for a secondary battery was prepared as follows. First, fibrous carbon dispersion 1 was placed in a stainless steel container, and NMP was added while stirring with a disperser, and the mixture was stirred for 30 minutes. Next, NMC and the above dispersion were charged into the container of a planetary mixer (Hibismix (R) 2P-1 type, manufactured by Primix Corporation), and the mixture was stirred for 120 minutes at a rotation speed (revolution) of 20 rpm. The mixture was in a non-slurry state during stirring. The temperature was controlled at 25°C with a temperature-controlling chiller during stirring. After that, the obtained mixture was taken out into a stainless steel vat and dried at 120°C for 2 hours using a hot air dryer to completely remove the liquid components. The dried product was coarsely crushed in a mortar to obtain electrode composite for a secondary battery 1.

[0203] (Examples 1-2 to 1-13) According to the compositions shown in Table 3, Composites 2 to 13 were obtained in the same manner as in Example 1-1.

[0204] (Comparative Example 1-1) An electrode composite for secondary batteries was produced as follows according to the composition shown in Table 3. NMC and fibrous carbon were charged into a container of Mechanofusion (AMS-MINI, manufactured by Hosokawa Micron Corporation) and stirred at a rotation speed of 7000 rpm for 10 minutes to obtain electrode composite for secondary batteries 14. During stirring, the temperature was controlled at 25°C with a temperature-controlling chiller. (Comparative Example 1-2) According to the composition shown in Table 3, an electrode composite for a secondary battery was prepared as follows. First, the fibrous carbon dispersion 1 was placed in a stainless steel container, and NMP was added while stirring with a disperser, and the mixture was stirred at 5000 rpm for 30 minutes. Next, NMC and the above dispersion were charged into the container of a planetary mixer (Hibismix (R) 2P-1 type, manufactured by Primix Corporation), and the mixture was stirred for 90 minutes at a rotation speed (revolution) of 30 rpm to prepare a slurry-like mixture. During stirring, the temperature was controlled at 25 ° C. with a temperature-controlling chiller. After that, the mixture obtained was taken out into a stainless steel vat and vacuum-dried at 110 ° C. for 3 hours using a vacuum dryer to completely remove the solvent. The dried product was coarsely crushed in a mortar to obtain an electrode composite for a secondary battery 15.

[0205] <Exothermic peak temperature of fibrous carbon> The exothermic peak temperature of the fibrous carbon was evaluated using a differential thermobalance ThermoplusEV02TG8121 manufactured by Rigaku. The exothermic peak temperature obtained when the temperature was increased from 40°C to 800°C at 10°C / min while flowing compressed air at 200mL / min was used as an index. The exothermic peak temperature was calculated by reading the peak top temperature of the exothermic peak of the fibrous carbon in the range of 400 to 700°C in the DTA curve obtained by measurement, as shown in FIG. 1 as an example.

[0206] <Powder resistance of composites> The powder resistivity of the composites was evaluated using a powder resistivity measurement system MCP-PD600 manufactured by Nitto Seiko Analytech Co., Ltd. Measurements were performed using a four-point probe method with a low-resistance powder probe, and the volume resistivity when a load of 20 kN was applied to each sample was used as an index.

[0207] <Evaluation of the state of fibrous carbon in composites> The dispersion state of the fibrous carbon in the composite was determined using a JEOL JSM-7800F scanning electron microscope. Criteria for determining the surface disintegration state of fibrous carbon active material ◎: The area of ​​fibrous carbon adsorbed on the active material in a crushed fiber state is 50% or more of the entire surface area of ​​the active material. ○: The area of ​​the fibrous carbon adsorbed on the active material in a crushed state is 10% or more and less than 50% of the entire surface of the active material. ×: The area of ​​the fibrous carbon adsorbed on the active material in a crushed state is less than 10% of the entire surface of the active material.

[0208] [Table 3]

[0209] The abbreviations used in Table 3 have the following meanings: NMC: S800 (LiNi 0.8 Mn 0.1 Co 0.1 O2, manufactured by Ningbo Ronbay New Energy Technology Co., Ltd.

[0210] As shown in Table 3, the examples showed superior composite state and powder resistance of the fibrous carbon compared to the comparative examples. The fibrous carbon in the composite of the examples was loosened and adsorbed on the surface of the active material without excessive aggregation, and a conductive path in the composite could be uniformly formed. This is thought to be because the adsorption force to the fibrous carbon was improved by compounding the fibrous carbon dispersion in which the electrode active material and the fibrous carbon were dispersed in a solvent in a non-slurry state using a mechanochemical mixer, and aggregation of the fibrous carbon was suppressed during the process of mixing the composite and the process of drying the solvent. On the other hand, in the comparative example, insufficient crushing of the fibrous carbon during the manufacturing process of the composite and excessive drying and aggregation during the drying process resulted in a decrease in the amount of adsorption onto the active material surface and uneven distribution of the material, which is thought to have resulted in uneven formation of conductive paths in the composite. From the above, by using the composite of this example as a composite for an electrode, it is expected that the electrode resistance can be reduced and the rate characteristics and cycle characteristics of the battery can be improved.

Claims

1. A method for producing a composite for a secondary battery electrode, comprising: The method includes a step of combining an electrode active material and a fibrous carbon dispersion in which fibrous carbon is dispersed in a solvent in a non-slurry state using a mechanochemical mixer, and a step of removing the solvent and drying the resulting mixture, The fibrous carbon dispersion includes fibrous carbon, a dispersant, and a solvent, The dispersant comprises a copolymer A containing a nitrile group-containing structural unit and an aliphatic hydrocarbon structural unit, The Mooney viscosity (ML 1+4 , 100°C) is 10 to 70, The method for producing a composite for a secondary battery electrode, wherein the fibrous carbon dispersion has a phase angle of 19° or more at a frequency of 1 Hz as measured by dynamic viscoelasticity measurement.

2. The method for producing a composite for a secondary battery electrode according to claim 1 , wherein the complex modulus of elasticity of the fibrous carbon dispersion is less than 20 Pa as determined by dynamic viscoelasticity measurement.

3. 3. The method for producing a composite for a secondary battery electrode according to claim 1, wherein the content of the nitrile group-containing structural unit is 15 mass% or more and 50 mass% or less, and the content of the aliphatic hydrocarbon structural unit is 40 mass% or more and less than 85 mass%, based on the mass of the copolymer A.

4. 3. The method for producing a composite for a secondary battery electrode according to claim 1, wherein the composite for a secondary battery electrode has an exothermic peak temperature of 520° C. or less, as determined by simultaneous thermogravimetry and differential thermal analysis under an oxygen atmosphere, and a volume resistivity of 100 Ω cm or less under a load of 20 kN.

5. 3. The method for producing a composite for a secondary battery electrode according to claim 1, wherein the composite for a secondary battery electrode contains a binder resin.

6. A method for producing an electrode film, comprising: preparing an electrode composite for a secondary battery according to the method according to claim 1 or 2; and forming an electrode film using the electrode composite for a secondary battery.

7. A method for producing a secondary battery, comprising: preparing an electrode composite for a secondary battery according to the method according to claim 1 or 2; and forming an electrode film using the electrode composite for a secondary battery.

Citation Information

Patent Citations

  • Hydraulic clutch switch valve

    JP1978077946A

  • Optical processing apparatus

    JP1988080526A

  • Active material and battery using the same

    JP2016201228A

  • Composite particles for electrochemical element electrodes, electrochemical element electrodes, and electrochemical elements

    JP6954424B2

Cited By

  • Steel for bolts

    CN122996213A

  • Bolt steel

    WO2025205227A1